Proactive education as a dynamic strategy to strengthen the high school teaching and learning process - Leila Lucia Moreira Morales, Robertson Xavier Calle García (International Journal of Advanced Science and Technology, 2020)
Motivation of students towards educational activities, reflected in low school performance, accompanied by harmful and uncompromising actions of changes favorable to a prominent life, as well as the ethical degradation of some teachers has evidenced the need to promote changes aimed at the development of positive attitudes that stimulate the interest of teachers and educating to transform and energize the teaching and learning process. Proactive education is a type of training, in which the authors of the teaching and learning process become active participants in transformative instruction, for which it is necessary for teachers to structure favorable learning environments, incorporate active techniques according to the chronological and cognitive abilities of the student, that promote collaborative learning, favoring criticality and autonomy. The objective of the research is to propose a proactive education as a dynamic strategy to strengthen the high school teaching and learning process. The development of this article corresponds to a bibliographic research, supported by the inductive-deductive methodology based on an exegetical review of scientific articles and reliable texts to provide academic rigor to the research. Among the results, the need to promote favorable spaces to promote the combination and interaction of situations and social interactions that can enhance dynamic, interactive, reflective, collaborative and experiential learning for students.